Asymmetric supercapacitor based on nanostructured porous manganese oxide and reduced graphene oxide in aqueous neutral electrolyte. (July 2017) - Shivakumara, S.; Munichandraiah, N.
Abstract: A High energy, asymmetric supercapacitor (ASC) has been constructed using porous manganese oxide (MnO2 ) nanostructures as positive electrode and reduced graphene oxide (RGO) as negative electrode in 1 M Na2 SO4 electrolyte. The ASC device exhibits excellent electrochemical performance, when the device is assembled with optimal mass ratio. The energy density is 22.2 W h kg −1 at a power density of 101 W kg −1, when the device is cycled reversibly in the high potential range of 0–2 V. The asymmetric supercapacitor device also exhibits a superior cycling stability with 90% retention of the initial specific capacitance after 3000 cycles. Highlights: The ASC uses nanostructured MnO2 and stacked RGO as the positive and negative electrodes, respectively. The ASC shows a specific capacitance in an aqueous Na2 SO4 solution. The ASC shows high power density by operating at a cell voltage of 2.0 V. The ASC system demonstrate a stable charge/discharge cycle behavior up to 3000 cycles when the cell is operated at a voltage window of 2.0 V.